Prospective evaluation of unsuspected pulmonary embolism on contrast enhanced multidetector CT (MDCT) scanning - Ritchie, Gillian (BMJ Group, 2007)
AIM: To quantify the incidence of unsuspected pulmonary emboli (PE) in an unselected inpatient population undergoing contrast enhanced multidetector CT (MDCT) scanning of the thorax and to assess aetiological factors in their development. METHODS: All inpatients undergoing MDCT scanning of the thorax over a 10 month period were prospectively identified. Patients with previous or suspected current PE were excluded. CT scans were reviewed and the degree of contrast enhancement and presence of PE recorded. Where PE was found, the level of the most proximal thrombus was identified. Patient age, length of admission, slice scan thickness and clinical indication were noted. RESULTS: 547 inpatients who had undergone MDCT scanning were identified. Following exclusions 487 remained, 28 of whom (5.7%) had PE. Unsuspected PE was more common with increasing age, occurring in 9.2% (20/218) of all patients over 70 years and 16.7% (11/66) of those over 80 years (p<0.001). Eighteen of the 28 positive scans (64.3%) were at the segmental or subsegmental level. No other aetiological factor was identified which significantly increased the incidence of unsuspected PE. No significant difference was noted between 4‐slice and 16‐slice MDCT. Nine of the cases of incidental PE (32.1%) were not identified by the original reporting radiologists. CONCLUSION: PE is an unsuspected finding on contrast enhanced MDCT scanning of the thorax in 5.7% of all inpatients. The incidence is higher in older patients. Most are peripheral and >30% are missed on initial review. PE should be routinely sought in all contrast enhanced MDCT scans of the chest, irrespective of the indication for the CT scan.